THE ANTI-CORRUPTION STRUGGLE OF UZBEKISTAN AND THE IMPORTANCE OF ITS IMPROVEMENT. - Aminova Manzura Mutalibovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the course of the fight against corruption in Uzbekistan, the significance of the law “On Combating Corruption” adopted in the country. The author cited specific sources that this law marked the beginning of a new anti-corruption period. In the article, the Author highlighted the assessment of the President of the Republic of Uzbekistan of corruption, as well as the essence of the issued decrees and decisions to combat it. The article also refers to the accession of Uzbekistan to the UN Anti-Corruption Convention on Combating Corruption at the International Level (New York, October 31, 2003), as well as membership in the International organization Transparency International. This organization includes 180 countries located in different regions of the Earth, and it is evaluated on a 100-point system in accordance with the Corruption Perceptions Index. The article reveals the positive reasons for the growth of the rating indicators of Uzbekistan, established by Transparency International. But still, the facts prove the presence of corruption crimes in the country. In the article, the author offers his recommendations of 11 points to improve the effectiveness of the fight against corruption.